2014
DOI: 10.2478/s11686-014-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the head of Scomber colias (Osteichthyes: Scombridae) from the western Mediterranean Sea

Abstract: The metazoan parasite assemblage of the head of 30 specimens of the Atlantic chub mackerel (Scomber colias) from the western Mediterranean Sea was analysed. Eight species of parasites were found, four mazocraeid monogeneans: Grubea cochlear (prevalence = 10%), Kuhnia scombercolias (59%), K. scombri (52%), Pseudokuhnia minor (86%); three didymozoid trematodes: Nematobothrium cf. faciale (21%), N. filiforme (41%), N. scombri (7%); and one laerneopodid copepod: Clavelissa scombri (7%). Results were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This is in accordance with other studies on scombrids, e.g. Scomber colias that showed differences in the helminth fauna between the opposite sides of the Atlantic Ocean (Mele et al 2014). Moreover, the difference between the Atlantic and Mediterranean domains can influence the dispersion and recruitment of the generalist parasites infecting large migrant fish, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with other studies on scombrids, e.g. Scomber colias that showed differences in the helminth fauna between the opposite sides of the Atlantic Ocean (Mele et al 2014). Moreover, the difference between the Atlantic and Mediterranean domains can influence the dispersion and recruitment of the generalist parasites infecting large migrant fish, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…worldwide were used to assess the dissimilarity between the parasite faunas of the head region of the bullet and frigate tunas from four geographical regions: A. thazard from the Atlantic Ocean (data from Vervoort, 1965; Fuentes Zambrano, 1997; Mogrovejo et al , 2004; Chisholm & Whittington, 2007), A. thazard from the Indian Ocean (data from Silas, 1962; Mogrovejo et al , 2004; Chisholm & Whittington, 2007), A. thazard from the Pacific Ocean (data from Silas, 1962; Yamaguti, 1970; Mogrovejo et al 2004; Chisholm & Whittington, 2007) and A. rochei from the Mediterranean Sea (present results). Parasite fauna dissimilarity was evaluated with the Marczewski–Steinhaus distance (‘cc’ method, ‘betadiver’ function, ‘vegan’ library of the R-software) and the Bray–Curtis index (‘–1’ method, ‘betadiver’ function, ‘vegan’ library of the R-software) (Culurgioni et al , 2014; Mele et al , 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Some genetic studies showed no significant differences between the Atlantic chub mackerel from the Mediterranean and eastern Atlantic areas (Scoles et al 1998, Zardoya et al 2004). However, significant regional differences have been found between smaller areas in the east Atlantic Ocean, including the Mediterranean Sea and Macarronesian islands, based on the analysis of morphology, meristic characteristics (Allaya et al 2016, Bouzzammit and El Ouizgami 2019, Muniz et al 2020) and associated parasites (Mele et al 2014). Muniz et al (2020), based on otolith morphology analysis, suggested the existence of one group in the northeast Atlantic islands (Azores, Madeira and the Canary Islands) and another one on the Iberian Portuguese coast.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, morphologic and parasite studies have shown significant differences between Atlantic chub mackerel from the western Atlantic and the eastern Atlantic (Scoles et al 1998, Roldán et al 2000, Costa et al 2011, supporting the existence of two different populations at either side of the Atlantic Ocean. However, whether this species constitute a single stock or not in the eastern Atlantic is still unknown, as the studies performed in this area provide conflicting results (Scoles et al 1998, Mele et al 2014, Muniz et al 2020). The information available on the northeast Atlantic suggests that in both African and European waters the species migrates from the wintering areas (mainly located in Mauritanian waters, southern Portugal and the inner part of the Bay of Biscay) towards northern waters in summertime and, in the case of the Bay of Biscay, towards the western Iberian Peninsula (ICES 2021a).…”
Section: Introductionmentioning
confidence: 99%